Comparison of Pharmacokinetics and Biodistribution of 10-Deacetylbaccatin III after Oral Administration as Pure Compound or in Taxus chinensis Extract: A Pilot Study - Zhang, Xueli; Lv, Jiajia; Wang, Liling; Shao, Hua (Planta Medica, 2016)
Taxanes are a class of bioactive compounds isolated from the Taxus species. 10-Deacetylbaccatin III is one of the popular taxane compounds with antitumor activity, but the pharmacokinetic profile of this compound remains elusive. Previously, we prepared the taxane fractions from the twigs and leaves of Taxus chinensis var. mairei containing 20.4 % 10-deacetylbaccatin III. This study aimed to investigate the pharmacokinetics of 10-deacetylbaccatin III and biodistribution, and explore the potential changes when it was administered in the form of taxane extracts. A simple, sensitive, and reliable liquid chromatography-tandem mass spectrometry method was developed and validated for the quantitative determination of 10-deacetylbaccatin III in biosamples. The results showed that 10-deacetylbaccatin III, after oral dosing, displayed a quick absorption into the blood and distribution into major organs. Oral administration of 10-deacetylbaccatin III in the form of taxane mixtures led to a 16-fold increase in the systemic exposure of pure 10-deacetylbaccatin III, with the AUC0-U in the plasma increasing from 25.75 ± 11.34 to 231.36 ± 70.12 µg h/L (p < 0.0001). Moreover, the concentrations of 10-deacetylbaccatin III in major tissues were significantly enhanced when given in taxane extracts. These findings revealed pharmacokinetic interactions in the taxane components from T. chinensis var. mairei, which contributed to an enhanced systemic exposure of pharmacologically active taxanes.
Keywords: Taxus chinensis; Taxaceae; 10-deacetylbaccatin III; pharmacokinetic interactions; taxanes